A Study of the Initial Stages of Co Deposition on a Silver Electrode in Ammonia Medium Using an Electrochemical Quartz Crystal Microbalance. (31st January 2013) - Montes-Rojas, A.; Donjuan-Medrano, A. L.
Abstract : The early stages of Co deposition on a silver electrode in ammonia medium were studied using cyclic voltammetry and chronoamperometry coupled with quartz crystal microbalance (EQCM) in ammonia solution. The results obtained by means of EQCM showed that during the initial stages of cobalt deposition a monolayer is formed on the substrate both in the underpotential and overpotential region, and this monolayer is formed at −600 mV and −980 mV. Once the cobalt deposition process starts, the growth is very fast making the investigation of the initial stages rather difficult. During this process, cobalt atoms transfer their two electrons through free species and not through cobalt hydroxide species adsorbed on the electrode as CoOH + or Co(OH)2 . In addition, it has been found that at potentials more positive than −600 mV, ammonia adsorption takes place on the substrate surface, and theses species are replaced when the cobalt atoms arrive at potentials more negative than −600 mV.